2023
DOI: 10.1519/jsc.0000000000004155
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition of Competitive Bodybuilders: A Systematic Review of Published Data and Recommendations for Future Work

Abstract: Bauer, P, Majisik, A, Mitter, B, Csapo, R, Tschan, H, Hume, P, Martínez-Rodríguez, A, and Makivic, B. Body composition of competitive bodybuilders: a systematic review of published data and recommendations for future work. J Strength Cond Res 37(3): 726–732, 2023—The purpose of this review was to systematically summarize studies measuring the body composition of competitive bodybuilding athletes to provide recommended values for preparation and during competition. The protocol was preregistered with PROSPERO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This was the result of the subject's disapproval of the process of collecting additional blood, and the results of the experiment are planned to supplement the reliability of the results in future follow-up studies on the premise of a high possibility. Lastly, we assessed body composition using bioelectrical impedance analysis (BIA), In-Body 770 equipment, which offers a time- (within 2 min) and cost-effective, and high reproducibility (coefficient of variation, < 5%) 65 68 . Unfortunately, however, it is important to note that In-Body 770, despite its advantages, has limitations as suggested by Brewer et al 69 .…”
Section: Discussionmentioning
confidence: 99%
“…This was the result of the subject's disapproval of the process of collecting additional blood, and the results of the experiment are planned to supplement the reliability of the results in future follow-up studies on the premise of a high possibility. Lastly, we assessed body composition using bioelectrical impedance analysis (BIA), In-Body 770 equipment, which offers a time- (within 2 min) and cost-effective, and high reproducibility (coefficient of variation, < 5%) 65 68 . Unfortunately, however, it is important to note that In-Body 770, despite its advantages, has limitations as suggested by Brewer et al 69 .…”
Section: Discussionmentioning
confidence: 99%
“…However, reducing carbohydrates of this magnitude close to the competition should only happen briefly to avoid muscle loss [ 26 ]. Furthermore, approaching the competitive phase, a 5–6% reduction in body fat mass is sought; therefore, the total energy intake is reduced, and proteins and fats are modulated [ 27 ]. Increasing the protein content during diets with energy deficit regimes allows the maintenance of muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, maintaining resistance training levels and increasing protein intake is an established procedure. However, the increase in aerobic exercise [ 27 ] for greater muscle definition may lead to a depletion of muscle glycogen with a consequent reduction in the volume of muscle masses. At the same time, the reduction in carbohydrate intake could have the same effect as the reduction in muscle volume due to the reduced fluid recall exerted by the lower muscle glycogen content [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated energy needs of competitive bodybuilders were calculated using data from a recent systematic review by Bauer et al (2023) [48]. This systematic review included 16 studies that reported anthropometric data from 235 healthy male competitive bodybuilders with previous competition experience or currently in preparation for their first competition and who were not seeking weight loss [48]. The age range of these athletes was 22 to 35 years.…”
Section: Methodsmentioning
confidence: 99%
“…For this modeling analysis, the nutrient needs of competitive bodybuilders were chosen because their professional success depends predominantly on their ability to maximize skeletal muscle mass [ 45 , 46 ]. Male bodybuilders were selected as the population of interest because female bodybuilders typically require less total protein intake due to their lower mean body mass [ 47 , 48 ]. There is a common belief that athletes and other individuals pursuing increased muscle mass while following plant-based diets require protein supplementation [ 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%